Community Perceptions on Sungai Tohor Village Forest, TebingTinggi Timur Subdistrict, Kepulauan Meranti Di - Haris Aulia Reza; Nurul Qomar; M. Mardhiansyah (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2023)
The Social Forestry Program will open up opportunities for communities around the forest to apply for forest management rights to the government. Sungai Tohor Village has received forest management rights from the Ministry of Environment and Forestry. The management of Sungai Tohor village forests is an important access for local people to manage forests sustainably. This study aims to determine the perception of the community on the management of Village Forests. Data was collected in several ways: closed interviews, open interviews, field observations, and documentation studies. Respondents from the community as many as 39 people were calculated by the Slovin formula. The results showed that the community knows what the functions and benefits of the Village Forest. Most people have a positive perception of Sungai Tohor Village Forest, 97.43% of respondents strongly agree on the function of village forests and 100% of respondents strongly agree with the benefits of village forests.